Perancangan UI/UX pada Toko Rental Outdoor Adventure Sphere Metode Design Thinking - Setiawan Adib Wibowo; Dwi Setiaji; Khaidir Umar; Ghulam Vicco Febrianta; Indrawan Ady Saputro (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The development of the digital economy in developing countries is expected to encourage economic growth, increase resources and workforce efficiency, provide access to international markets, and reduce transaction costs. The research aims to offer practical and affordable solutions for those who want to explore nature without having to buy their own equipment and provide information and advice on destinations, safety tips and equipment guides, as well as supporting the adventure community. This design uses the Design Thinking method, which is an iterative process that aims to understand users, define problems in depth, and find solutions that meet their needs. The result of this research is the Adventure Sphere Application Prototype, which contains profile, homepage, product display, basket and product video features. It is hoped that this application will make it easier for buyers to rent outdoor equipment and this application will also provide useful information to renters regarding the use of outdoor equipment.